The effects of using an online collaboration tool on college students' learning of academic writing skills. (April 2022) - Li, Jia; Mak, Lillian
Abstract: Expository writing skills, integrating perspectives and evidential supporting sources, are critical for students to succeed in college. However, many students at the onset of postsecondary education lack adequate reading and writing skills to complete integrated language tasks, including paraphrasing and synthesizing information critically and coherently from multiple sources to elicit deep thinking and make sophisticated arguments. This article reports on a 10-week intervention using a cloud-based technology application to support students' collaboration in reading-to-write learning tasks. The intervention focused on systematically helping students develop distinct expository writing skills progressively with embedded reading strategies. Sixty-nine first-year students enrolled in an English course at a large Canadian community college participated in the study. The scores of pre- and post-writing tests and standardized reading tests measuring three reading attributes were analyzed to examine the control and treatment groups' performance. A statistically significant result was found in the writing scores of the treatment subgroup with lower language proficiency levels, indicating that the instructional framework with the technology-supported collaborative setting had a positive effect. This study provides evidence that college students with underdeveloped language skills can benefit from a well-structured, online intervention supporting a collaborative learning environment for academic writing. Highlights: Cloud technology tools can effectively support lower proficiency students' reading-to-write practice in groups. Well-structured, online interventions benefit low-proficiency students by supporting their collaborative writing practice. Technology-based writing instruction leveraging peer support is the most effective with students with varying proficiencies.